APPLICATION OF ACTIO INIURIARUM WITH EX ANTE AND EX POST APPROACHES TO LOVE SCAMMING CASES IN INDONESIA - Alisah, Siti; Kusuma Putri, Riski Ananda (Hukum Responsif, 2025)
Love scamming is a form of emotional relationship-based crime that develops along with the advancement of information technology. This mode exploits the victim's emotional needs through the manipulation of online romantic relationships for financial gain. Unfortunately, Indonesia's legal system still primarily focuses on material losses and has not adequately accommodated non-material losses, such as honor, self-esteem, and emotional injury. This research employs normative juridical methods, incorporating legislative and conceptual approaches, to examine the potential application of the principle of actio iniuriarum within the context of Indonesian law. This approach not only emphasizes the element of violation of personality rights, but also allows for the award of non-material compensation in the form of solatium. By integrating the ex ante (assessment of risk and malicious intent before harm occurs) and ex post (evaluation of post-breach emotional harm), the study offers a more holistic and adaptive model of legal protection. The results of the study show that actio iniuriarum has the potential to be a relevant alternative mechanism to answer the void of legal protection for digital-based emotional crimes.